Procalcitonin for predicting catheter-associated bloodstream infection: A meta-analysis - Jia, Chun Mei; Feng, Shun Yi; Li, Yong; Cao, Zong Xun; Wu, Cheng Pu; Zhai, Yan Zhao; Cui, Jie; Zhang, Meng; Gao, Jie (Medicine (Baltimore), 2019)
The predictive accuracies of procalcitonin (PCT) in the diagnosis of catheter-associated bloodstream infection (CABSI) vary widely. This meta-analysis aimed to explore the predictive value of PCT for CABSI. We searched PubMed, EMBase, Web of Science, ScienceDirect, Cochrane Library, and studies published up to 10 March 2019. Odds ratios (ORs) with 95% confidence intervals (95%CIs) were calculated to evaluate PCT predictive value using Stata 14.0 software. The meta-analysis was composed of 7 studies, consisting of 347 subjects. Pooled analysis demonstrated that a high PCT was significantly correlated with CABSI (pooled OR = 23.36, 95%CI 12.43-43.91, P < .001) and medium heterogenicity (I = 36.9%, P = .147). The pooled sensitivity and specificity were 85% (95%CI 0.76-0.91) and 89% (95%CI 0.68-0.97), respectively. Although Begg funnel plot (P = .007) indicated the presence of publication bias among the included studies, the stability of the pooled outcomes was verified by the trim-and-fill method. Furthermore, sensitivity analyses did not show important differences in effect estimation. PCT is an effective predictor of CABSI. However, high-quality randomized controlled trials are needed to determine whether PCT could predict CABSI.